The Ministry of Trade and Industry Decree No. 1254 of the Year 2017 On Extending the Period of Imposing Temporary Anti-Dumping Duties on Imports of Steel Rebar Item (Coils, Rods and Bars) Originating or imported from China, Turkey and Ukraine = وزارة التجارة والصناعة قرار رقم 1254 لسنة 2017 بمد فترة تطبيق رسوم مكافحة الإغراق المؤقتة على الواردات من صنف حديد التسليح (أسياح ولفائف وقضبان وعيدان) ذات منشأ أو المصدرة من الصين وتركيا وأوكرانيا - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic